Pengawasan Pemerintah dan Masyarakat terhadap Usaha Karaoke di Kabupaten Grobogan - Kusumastuti, Niken Tyas; Widayati, Wiwik; Astrika, Lusi (Journal of Politic and Government Studies, 2015)
Supervision is an activity plan for monitoring an object in order to avoid distortions. As businesses karaoke, karaoke is an entertainment venue which is now starting to bloom and loved by the people in Grobogan the number of unlicensed karaoke higher than the licensed karaoke. So there are deviations of the policies that have been set by the government.Supervision of karaoke in Grobogan is important because to maintain the security environment in the community both in terms of morals, ethics and religion. In this study, researchers used a qualitative research method using descriptive methodsBased on the results it was concluded that the imbalance of supervision by the government. Where supervision is more emphasis on preventive contro l, ie the licensing mechanism. While on supervision repressive enough in enforcing the rules / policies.The recommendation that can be delivered include government and society should jointly supervise the presence of karaoke to maintain the security and comfort of the environment. In addition, the government should increase the level of supervision of the karaoke especially in repressive surveillance.